Urgensi Pendidikan Karakter Dalam Menciptakan Masyarakat Berkarakter - Alivia Fitri Salsabila; Muhammad Atma Taher; Rehnaningtyas Rehnaningtyas; Ratna Sari Dewi (International Forum of Researchers and Lecturers, 2023)
To build a community with character, this research seeks to evaluate and provide an overview of the Basic Concepts of a Community with Character and Strategies for Building a Community with Character. Researchers apply qualitative methods to collect data to study the purpose of the matter. This approach requires searching for references in papers and other references that are treated preferably as substitutes. The results of the research and subsequent discussion show how important character is, not only at school but also at home and in society. Character is an important component in people's lives because it allows us as a society to be meaningful for individuals and citizens, so strategies for building a community with character are important. If Character Education is carried out as a whole starting from home, school, and community it can be successful and effective. As a result, the character is a component of culture and community identity, their behavior will reflect that.